Variant Ciz1 is a circulating biomarker for early-stage lung cancer - Higgins, Gillian; Roper, Katherine M; Watson, Irene J; Blackhall, Fiona H; Rom, William N; Pass, Harvey I; Ainscough, Justin F. X; Coverley, Dawn (Proceedings of the National Academy of Sciences - PNAS, 2012)
There is an unmet need for circulating biomarkers that can detect early-stage lung cancer. Here we show that a variant form of the nuclear matrix-associated DNA replication factor Ciz1 is present in 34/35 lung tumors but not in adjacent tissue, giving rise to stable protein quantifiable by Western blot in less than a microliter of plasma from lung cancer patients. In two independent sets, with 170 and 160 samples, respectively, variant Ciz1 correctly identified patients who had stage 1 lung cancer with clinically useful accuracy. For set 1, mean variant Ciz1 level in individuals without diagnosed tumors established a threshold that correctly classified 98% of small cell lung cancers (SCLC) and non-SCLC patients [receiver operator characteristic area under the curve (AUC) 0.958]. Within set 2, comparison of patients with stage 1 non-SCLC with asymptomatic age-matched smokers or individuals with benign lung nodules correctly classified 95% of patients (AUCs 0.913 and 0.905), with overall specificity of 76% and 71%, respectively. Moreover, using the mean of controls in set 1, we achieved 95% sensitivity among patients with stage 1 non-SCLC patients in set 2 with 74% specificity, demonstrating the robustness of the classification. RNAi-mediated selective depletion of variant Ciz1 is sufficient to restrain the growth of tumor cells that express it, identifying variant Ciz1 as a functionally relevant driver of cell proliferation in vitro and in vivo. The data show that variant Ciz1 is a strong candidate for a cancer-specific single marker capable of identifying early-stage lung cancer within at-risk groups without resort to invasive procedures.